Sport in the county of Kremenets in the light of "Życie Krzemienieckie" magazine (1932-1939) - Eligiusz Małolepszy; Teresa Drozdek-Małolepsza (Jan Długosz University in Częstochowa, 2019)
The aim of the study was to present the sports movement in the county of Kremenets in the light of "Życie Krzemienieckie" ["Life of Kremenets"] magazine. "Życie Krzemienieckie" was a social magazine published mainly as a monthly in the years 1932-1939. In addition to social, economic and cultural issues it also addressed subjects related to the sports movement, mainly in the community of the county of Kremenets. The issue of sport was actually discussed in every issue of the magazine. In terms of sporting activities it dealt with matters connected with sports infrastructure, personnel training, organization and management of sport, school sports and athletic competition. An important role in terms of sports movement conditions in the county of Kremenets was played by local sport management structures, including: County Committee for Physical Education and Military Training and Municipal Committee for Physical Education and Military Training. On the territory of the county of Kremenets a huge role as regards the development of sports infrastructure, personnel training or organization of sports events was attributed to the Union of Social Organizations. Articles, materials and coverage mainly related to winter sports, sports games, water sports, and gliding. Sport was practised in the activities of social organizations, such as the Volhynian Association of Rural Youth, Polish Scouting and Guiding Association and the Shooting Association.